Aplicación del método de plasma-trombina al diagnóstico de enfermedades parasitarias - De Girolami, Ettore (1988)
Four cases of parasitic diseases have been diagnosed by preparing samples with the plasma-thrombin cell block technique. This method has been previously applied for the cytological detection of cancer.The authors want to emphasize that by applying this method to samples obtained from parasitized organs, it is posible to diagnose easily the disease as well as to study, by means of pseudotissural preparations, the tissues response to the parasite and, with follow up samples, the progression of the disease itself.